Role of nurse preceptors in the clinical learning environment for undergraduate nursing students at selected health facilities in Central and Eastern Kenya - Kapigen, Millicent; Kangethe, Simon; Sum, Tecla (African Journal of Science, Technology and Social Sciences, 2025)
To precept means mentoring or instructing someone. The clinical nurse preceptor instructs, coaches and supervises nursing students. The role of a nurse preceptor is an experiential teaching strategy that lasts for sometime and involves a nurse who is experienced in nursing practice working individually with nursing students. The main objective of this study was to assess the role of nurse preceptors in the clinical learning environment for undergraduate nursing students at selected health facilities in Central and Eastern Kenya. was collected from nurses who were directly involved with undergraduate nursing students’ clinical learning environment. 153 nurses from Meru, Nyeri and Chuka Teaching and Referral Hospitals and a structured questionnaire was used to obtain the data. Descriptive statistics was used to analyse data and presented in frequencies and percentages using tables and graphs. The response rate was 91.5%. 96 (68.6%) were female while 44(31.4%) were male. The majority of the respondents 137(97.8%) indicated that their role was to welcome and orient students in the clinical learning environment. Other roles mentioned were mentoring and supervising students; interact with students in a friendly manner as mentioned by 129(92.1%) of the respondents. 126(90.0%) of the respondents mentioned inducting new students while 117(83.5%) mentioned assigning duties as per clinical objectives. Nurse preceptors were aware of many roles in the clinical learning environment for undergraduate nursing students. They were aware that they were responsible in moulding a nursing student to be a competent professional nurse. The nurse preceptor should be aware of the students’ learning objectives in order to be effective in their preceptorship. They should be knowledgeable, skilled with critical thinking and decision-making skills that enable them to prepare students to be professional nurses in future. Therefore, nurse preceptor’s roles should be well defined to them.